Bioquímica e fisiologia da soja em ambiente protegido sob variações de déficit hídrico, xenobiótico e bioestimulante - Schneider, Julia Renata (2019)
Water deficit stress is the one of main occurrence and the one that most affects plant development. Fungicide application protects plants, but can lead to oxidative stress because it is a xenobiotic, compound strange to the plant. Under field conditions, plants are exposed to combinations of biotic and abiotic stresses, such as combined deficit water and fungicide application. The challenge of scientific research is characterize these processes and create management strategies to mitigate metabolic and economic effects. Also, to minimize the impacts of these stresses has been highlighted the use of biostimulant products, which act to induce plant defenses. Thus, t he objective of this study is to evaluate the interactive effects on the biochemistry and physiology of soybean plants submitted simultaneously to fungicide application and water deficit conditions, and the possible attenuation of plant damage by the biost imulant application, in a controlled environment. Biochemical and physiological changes were evaluated in soybean plants submitted to eight, six, four and two days without irrigation (eight different soil water potentials: - 0.2286, -0.0332, - 0.0245, -0.0164, -0.0074, -0.0029, - 0.0018, and -0.0008 MPa), xenobiotic and biostimulant applications. Visual symptoms showed that under water deficit plants were wilted. Also, under low water availability, was reduced water status, gas exchange, photosynthetic pigments, quantum yield of photosystem II, and increased leaf temperature. Hydrogen peroxide production was increased under deficit water stress and in situ detection of this specie showed high efficiency of biostimulant in its elimination. This was evidenced by the concentration evaluation of the hydrogen peroxide in cells, which decreased by biostimulant application, as well as superoxide. Nearly 70% of membrane damage was observed for plants with less water availability. Lipid peroxidation was increased in plants under low water potentials and under xenobiotic application. Glutathione, component of the metabolism antioxidant non-enzymatic, was also increased in lowest potentials of soil water. Thus, it is possible to conclude that water deficit induced oxidative stress, by the increased production of reactive oxygen species, cellular and molecular damage, and induction of antioxidant defense metabolism, reduction of gas exchange, water status and photosynthetic efficiency. Xenobiotic application also caused changes, but with less intensity. Deleterious effects on the cells were more pronounced when application occurred in plants submitted to low availability of soil water. This indicates different responses to the combination of stresses. The biostimulant application attenuated the effects of water deficit and xenobiotic. Some situations have shown that the xenobiotic can influence the biostimulant action, if applied concomitantly.